When genes go wild: Highly variable internal transcibed spacer1 and conserved mitochondrial DNA haplotypes used to examine the genetic diversity and dispersal pathways of invasive Hylotrupes bajulus in Western Australia - Castalanelli, M.; Cunningham, R.; Davis, M.; Groth, David; Grimm, Michael (Wiley Online, 2013)
1 Hylotrupes bajulus (Linnaeus) is a cryptic insect pest of seasoned coniferous timber.In 2004, an incursion of Hylotrupes bajulus was discovered in Perth, WesternAustralia.2 Two genes, one mitochondrial (cytochrome oxidase subunit I; COI ) and one nuclear(internal transcribed spacer 1; ITS1) were used to infer the origin of this incursion,as well as to test the likely dispersal pathways and dispersal distances of H. bajulus.3 We sequenced and examined 1003 cloned ITS1 fragments and 170 COI fragmentsfrom 14 international and 156 domestic specimens. The ITS1 fragment wasextremely variable, with 94% of the sites polymorphic.4 To remove the variability and select only the informative polymorphisms principalcomponent analysis was employed. This resulted in the selection of eight informativesingle nucleotide polymorphisms and seven microsatellites, which were convertedinto 119 unique ITS haplotypes. In comparison, COI was highly conserved, yieldingonly four haplotypes.5 The data suggest at least three independent incursions, of which two containedthe same mitochondrial haplotype but different ITS1 sequences. The datasets werefurther scrutinized to estimate local dispersal distances. The results suggested thatindividuals were capable of dispersing >14 km, which is significantly further than previously reported